Fear Factor: Exploring Students’ English Language Anxiety in the English Friday Program - Putri, Pristiamar Vadma; Hanafi, Muhammad; Khotimah, Khusnul (ICONELT, 2024)
Exploring students’ English language in the English Friday program is important for students’ capability, especially in enhancing their vocabulary and their speaking. To decrease the students’ anxiety, this study explores students’ experiences and perceptions of English language anxiety within the "English Friday" program, utilizing a descriptive qualitative methodology with open-ended questions by using a case study approach. The research includes respondents from grades 7, 8, and 9, chosen based on their varying lengths of involvement in the program. Findings reveal that while many students appreciate the program and feel it enhances their English proficiency, anxiety remains a significant challenge. Students across all grades experience anxiety when speaking English, despite the program’s benefits in providing consistent practice and fostering a supportive environment. The study underscores the need for more structured approaches to reduce anxiety, suggesting that building students’ confidence through regular practice and a non-judgmental setting can be beneficial. These insights are crucial for developing more effective strategies to help students overcome English language anxiety and improve their speaking skills.